The contribution of Paul Hiebert to folk religion: a missiological study among the Dendis of North-East Benin - Bade, Michee Bakande (University of the Free State, 2022)
Paul Hiebert voer aan dat een van die redes waarom Christelike sendings misluk het of nie baie suksesvol was onder volksgodsdienstiges nie, is die voortdurende onkunde van die wêreldbeskouing van volksgodsdiens wat deur baie van die vroeë Westerse Christelike sendelinge gehuldig is (1982:35-47). Hy bou voort op die bevindinge van sy klassieke opstel oor die “uitgeslote middel”, deur ’n nuwe konsep en paradigma vir kruiskulturele sendings voor te stel – ’n drieledige siening van die heelal (1982:44-47). Eerstens, deur die Dendi-mense van Noordoos-Benin as konteks van die empiriese studie te gebruik, ondersoek hierdie navorsing die impak van ’n fenomenologiese studie van volksgodsdienssending onder volksgodsdienstiges. Die navorser argumenteer in hierdie navorsing dat die implikasies vir sendings van Hiebert se drieledige siening van die heelal, die ontwikkeling van twee teologiese konsepte is: “’n teologie van die onsigbare” (Hiebert et al. 1999:370) en “’n teologie van die koninkryk van God.” (Love 2000:40; vgl. Bosch 1991:10; Glasser et al. 2003:74; Hiebert et al. 1999:25; Ott et al. 2010: 65, 315). Tweedens het hierdie navorser die Dendi-reaksies op geestelike aanvalle met ruqyah en adorcisme hersien en bespreek hoe ’n Christelike ritueel van eksorsisme hierdie Dendi-krisisrituele kan vervang. Die doel van hierdie studie was om te evalueer hoe lewenskrisisse of spesiale gebeurtenisse in die lewe van die Dendi-mense radikale verskuiwings of paradigmaverskuiwings vereis. Die etnografiese navorsing van hierdie studie het bestaan uit onderhoude wat in twee verskillende stede (Kandi en Malanville) gevoer is. Die data wat lukraak ingesamel is van 28 volwasse Dendi-mans en –vroue, is ontleed en geïnterpreteer met behulp van ATLAS.ti 9, ’n rekenaarondersteunde, kwalitatiewe, data-analise-sagteware (CAQDAS). Die kwalitatiewe data wat in die veld verkry is, het nie net die feit vasgestel dat die Islam wat deur die Dendi-mense beoefen word, steeds sterk beïnvloed word deur die Dendi-animistiese pre-Islamitiese wêreldbeskouing nie, maar dat ’n sendingstrategie wat fokus op die behoeftes wat mense ervaar, die doeltreffendste sou wees. Hierdie studie kom tot die gevolgtrekking dat die behoefte-benadering wat ervaar is om sendingwerk onder volksgodsdienstiges te doen, voorkeur moet geniet en aangemoedig moet word tydens Christelike sendings, want dit is Christologiese missiologie en holistiese sendingwerk wat lei tot wêreldbeskouingstransformasie en bekering: voldoen eers aan die behoeftes wat die mense ervaar en nooi hulle dan uit om Jesus te volg (Love 2000:91; Ott et al. 2010:276; White 1905:143).

𝑬𝒏𝒈𝒍𝒊𝒔𝒉 Hiebert contends that one of the reasons Christian mission has failed or not been very successful among folk religion, is the long ignorance of the folk religion worldview held by many of the early Western Christian missionaries (1982:35-47). Building on insights from his classic essay on the “excluded middle,” Paul Hiebert suggests a new concept and paradigm for cross-cultural mission–a three-tiered view of the universe (1982:44-47). Firstly, using the Dendi people of North-East Benin as the context of the empirical study, this research examined the impact of a phenomenological study of folk religion mission among folk religionists. The researcher argues in this research that the implications for missions of Hiebert’s three-tiered view of the universe is the development of two theological concepts: “a theology of the invisible” (Hiebert et al. 1999:370) and “a theology of the kingdom of God.” (Love 2000:40; cf. Bosch 1991:10; Glasser et al. 2003:74; Hiebert et al. 1999:25; Ott et al. 2010: 65, 315). Secondly, this researcher reviewed the Dendi responses to spirit attacks with ruqyah and adorcism and discusses how a Christian ritual of exorcism could replace these Dendi crisis rituals. The objective of this study was to evaluate how life crises or special events in the life of the Dendi people call for radical shifts or paradigm shifts. The ethnographic research of this study comprised interviews conducted in two different cities (Kandi and Malanville). The data randomly collected from 28 Dendi adult men and women was analyzed and interpreted using ATLAS.ti 9, a Computer Assisted Qualitative Data Analysis Software (CAQDAS). The qualitative data obtained from the field not only established the fact that the Islam practiced by the Dendi is still heavily influenced by the Dendi animist pre-Islamic worldview, but that a mission strategy that focuses on the people’s felt needs would be most efficient. This study concludes that the felt need approach to mission among folk religion should be preferred and encouraged in Christian mission, because it is Christological missiology, holistic mission, which leads to worldview transformation and conversion: first meet the felt needs of the people and then invite them to follow Jesus (Love 2000:91; Ott et al. 2010:276; White 1905:143). ___________________________________________________________________

Hiebert o hlahisa maikutlo ka hore le leng la mabaka a entseng hore barumuwa ba Sekreste ba se ke ba atleha haholo ka hara tumelo ya setjhaba, ke nako e telele ya ho nena tumelo ya setjhaba sa lefatshe ka bophara; ditjhaba tse neng di le matleng a barumuwa ba Sekreste ba Bophirimela, tsa nako ya kgalekgale (1982:35-47). Building o etsa tshusumetso e hlahisang lesedi ka bongodi ba meqoqo ya kgale bo bitswang “Excluded middle”. Paul Heibert o hlahisa mohopolo o motjha, katamelo le kutlwisiso ya bongodi ba diphuputso bakeng sa meetlo ya morero wa “a-three-tiered” ya bokahohle (1982:44-47). Ntlha ya pele, ho sebedisa setjhaba sa Dendi sa Bophirimela Botjhabela, Benin e le sebaka sa boithuto ba diphuputso tsa bopaki le teko le tekolo, diphuputso di hlahloba tshusumetso tsa boiphihlelo ba mofuputsi le bafuputsuwa ka tumelo ya batho ya bodumedi. Mofuputsi o hlahisa maikutlo diphuputsong tsena ka hore ditlamorao tsa morero wa Heibert tsa three-tiered ya bokahohle di ntsheditswe pele ke mohopolo wa Thutabomodimo: “Thutabomodimo ya tse sa bonweng” Hiebert le ba bang (1999:370) le “Thutabomodimo ya mmuso wa Modimo.” (Love 2000:40; cf. Bosch 1991:10: Glasser le ba bang 2003:74; Hiebert le ba bang 1999:25; le ba bang 2010:65, 315). Ntlha ya bobedi, mofuputsi o hlahlobile karolo ya Dendi ka ditlhaselo tsa moya tsa ruqyah le adorcism le ho hlalosa hore na meetlo ya Sekreste ya ho ntsha meya e ditshila e ka ba sebakeng sa e tlokotsing ya Dendi. Sepheo sa diphuputso tsena ke ho hlahloba hore na bophelo ba tlokotsi kapa bo ikgethang, ba diketsahalo tsa bophelo ba setjhaba sa Dendi bo ka bitsa diphetoho tse nang le sekgahla kapa katamelo le diphetoho kutlwisisong ya bongodi ba diphuputso. Diphuputso tsa tikoloho tsa boithuto bona di ne di kenyelletsa dipotso tsa patlisiso tse entsweng ditoropong tse pedi (Kandi le Malanville). Ditaba di bokelletswe ka lotho ho banna ba mashome a mabedi a metso e robedi ba Dendi le basadi, mme tsa manollwa le ho hlaloswa ho sebediswa A TLSA-TI9, khomputha e thusitseng ka mokgwa wa amnollo ya ditlhaloso tsa ditaba ka softewere (CAQDAS). Mokgwa wa tlhaloso ya ditaba o fumanweng tshebetsong ya Islamoe entsweng ke Dendi, o ntse o susumetswa lefatsheng, empa merero le maqiti e tsepameng ho setjhaba, e bone ditlhoko e le tsona tse bohlokwa. Diphuputso tsena di etsa qeto ya hore katamelo ya ditlhoko tsa merero hara ditumelo tsa setjhaba, e lokela ho tla pele mme ho kgothalletswe merero ya Sekreste hobane ke morero wa Sekreste o akaretsang merero e susumetsang phetoho le tshokoloho ya sebopeho sa lefatshe: ntlha ya pele; ho arabelwe ditlhoko tsa setjhaba le ho se memela ho latela Jeso (Love 2000:91; ott le ba bang. 2010:276; White 1905:143).
Thesis (Ph.D. (Practical and Missional Theology))--University of the Free State, 2022
Keywords: Hiebert, Paul G.; North-East Benin -- Dendi people; Missionaries -- Africa; Hiebert; Hiebert; Paul G; Paul G.; Noordoos-Benin - Dendi-mense; Noordoos-Benin - Dendi-mense; Sendelinge - Afrika; Sendelinge - Afrika; Hiebert; Paul G. Bophirimela Botjhabela Benin- -Setjhaba sa Denin; Baromuwa --Afrika